Edukasi Pencatatan Keuangan Sederhana dan Sosialisasi Koperasi Merah Putih sebagai Strategi Mendorong Ekonomi Berkelanjutan di Desa Badak: Pengabdian - Desi Nur Amelia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) in Badak Village aimed to address local economic challenges by improving financial literacy and strengthening community-based economic institutions. Despite its rich potential in agriculture, livestock, and micro-enterprises, the village faces obstacles such as poor financial management and inactive use of cooperatives. This program focused on two main initiatives: educating micro-entrepreneurs on basic financial record-keeping and promoting awareness of the Merah Putih Cooperative. Through interactive workshops and direct mentoring, participants learned how to record income and expenses, separate personal and business finances, and understand simple financial reporting. The cooperative socialization sessions helped build trust and interest in using cooperatives for shared economic benefit. As a result, the community showed increased awareness, improved financial behavior, and renewed interest in cooperative development. The program successfully laid the foundation for a more structured and collaborative village economy, contributing to long-term sustainable development.